Prevalence of latent TB infection among asylum seekers in emergency accommodation in Cologne, Germany: to the editor - Neuhann, Florian; Funke, Natalie; Bunte, Anne; Beiersmann, Claudia (ERJ Open Research, 2019)
Tweetable abstract ERSpublications - click to tweet∼12% of male asylum seekers from multiple countries were diagnosed with LTBI. Systematic documentation and reporting of LTBI, access to chemopreventive therapy, and early diagnosis of active TB are highly recommended for this vulnerable group. http://ow.ly/dVTp30onmaR
Gesehen am 12.11.2020